2018
DOI: 10.1016/j.jand.2017.11.021
|View full text |Cite
|
Sign up to set email alerts
|

Position of the Academy of Nutrition and Dietetics: The Role of Medical Nutrition Therapy and Registered Dietitian Nutritionists in the Prevention and Treatment of Prediabetes and Type 2 Diabetes

Abstract: It is the position of the Academy of Nutrition and Dietetics that for adults with prediabetes or type 2 diabetes, medical nutrition therapy (MNT) provided by registered dietitian nutritionists (RDNs) is effective in improving medical outcomes and quality of life, and is cost-effective. MNT provided by RDNs is also successful and essential to preventing progression of prediabetes and obesity to type 2 diabetes. It is essential that MNT provided by RDNs be integrated into health care systems and public health pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
68
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 142 publications
(72 citation statements)
references
References 75 publications
2
68
0
2
Order By: Relevance
“…In addition, two recent systematic reviews indicated that small improvements in weight loss and/or obesity can prevent the progression from prediabetes to type 2 diabetes over an extended period of time [ 21 , 22 ]. The results of our study are consistent with several previous studies [ 9 , 23 , 24 ]. Participants' anthropometric values and body composition measurements for weight, BMI and body fat decreased significantly from baseline to 3 months between groups, but the weight and body fat losses were modest.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…In addition, two recent systematic reviews indicated that small improvements in weight loss and/or obesity can prevent the progression from prediabetes to type 2 diabetes over an extended period of time [ 21 , 22 ]. The results of our study are consistent with several previous studies [ 9 , 23 , 24 ]. Participants' anthropometric values and body composition measurements for weight, BMI and body fat decreased significantly from baseline to 3 months between groups, but the weight and body fat losses were modest.…”
Section: Discussionsupporting
confidence: 94%
“…Nutrition therapy is an effective intervention for the management of prediabetes, especially the lifestyle changes based on dietary habits, which has increased dramatically in the US and worldwide over the last 30 years [ 8 ]. Strong evidence supports the role of dietary treatment provided by dietitians as being effective for managing prediabetes [ 9 ],which can even reverse the progress of diabetes. Among the various macronutrient proportions, a high carbohydrate content is a key risk factor for hyperglycemia since it is the greatest determinant of post-meal glycemia [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…There is a wealth of evidence demonstrating that dietary interventions are effective for the management of both type 1 and type 2 diabetes, for the prevention of type 2 diabetes, and there is now emerging evidence for the remission of type 2 diabetes [ 1 5 ]. Traditionally, it is recommended that nutritional advice is delivered by registered dietitians, and although there is evidence that dietitian-led interventions are more effective than those without input from dietitians [ 6 ], both the American Diabetes Association (ADA) and Diabetes UK recognise that other health professionals have a role in delivering dietary advice, ideally guided by a registered dietitian [ 1 , 2 ]. However, access to registered dietitians is limited, and a survey in the UK in 2002 reported that the level of dietetic support for those with diabetes was dramatically lower than recommendations, and had not increased since a survey conducted 5 years previously [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Major medical and health organizations agree that medical nutrition therapy provided by registered dietitians in adults with prediabetes or type 2 diabetes is clinically and cost effective. However, the barriers to accessing a specialist and problems with the reimbursement for services still exist [3]. Robbins et al [27] observed that only 9.1% of diabetic patients of the Philadelphia Health Care Centers had at least one nutritionist visit within a 9-year period.…”
Section: Current Difficulties and Perspectives For The Futurementioning
confidence: 99%